2015
DOI: 10.1177/0960327115584990
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of cholinesterase enzyme activity before and after exposure to organophosphate pesticides in farmers of a suburb region of Mazandaran, a northern province of Iran

Abstract: Introduction: Accidental toxicity by organophosphate (OP) agents may occur among farmers during spraying season due to improper use and handling. Plasma cholinesterase (ChE) activity measurement is recommended to monitor the extent of exposure to the OP agent. The aim of the current study was to measure plasma ChE activity before and after exposure with OP pesticides. Methods: This was a prospective study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 18 publications
1
9
0
3
Order By: Relevance
“…They found that hematological parameters such as hemoglobin (p= 0.002), hematocrit (p= 0.001), and prothrombin time (p= 0.001), were higher in farmworkers than in workers with other occupations. Pakravan et al [ 39 ] measured plasma cholinesterase activity before and after exposure to organophosphate pesticides in farmworkers. Based on their findings, pesticide exposure decreased plasma cholinesterase levels by 50%.…”
Section: Resultsmentioning
confidence: 99%
“…They found that hematological parameters such as hemoglobin (p= 0.002), hematocrit (p= 0.001), and prothrombin time (p= 0.001), were higher in farmworkers than in workers with other occupations. Pakravan et al [ 39 ] measured plasma cholinesterase activity before and after exposure to organophosphate pesticides in farmworkers. Based on their findings, pesticide exposure decreased plasma cholinesterase levels by 50%.…”
Section: Resultsmentioning
confidence: 99%
“…The non-specific biomarkers do not point to an individual cause of the effect, but they may reflect the total, integrated effect due, for instance, exposure to a mixture. Some early effect biomarkers have essentially been used as ‘exposure biomarkers’ in OSH e.g., cholinesterase activity for organophosphate pesticides [ 59 ], carboxyhaemoglobin for carbon monoxide [ 60 ]—these tend to be less generic markers so whilst still not specific they are focused on a group of chemicals with a common adverse effect. Both types of biomarkers of effect are useful indicators of early (critical) effects and can signal higher risks for a particular group of workers, helping to define priorities for preventive actions [ 58 ].…”
Section: Challenges For the Futurementioning
confidence: 99%
“…The rate of detoxification as well as duration of toxicity play important roles (Abdollahi et al, 2004[ 2 ]; Mostafalou et al, 2013[ 39 ]). There is clear evidence in the literature about the link between different pesticides exposure and occurrence of various human chronic diseases, such as cancer, Parkinson, Alzheimer, multiple sclerosis, diabetes, cardiovascular and chronic kidney diseases (Mostafalou and Abdollahi, 2017[ 37 ]; Souza et al, 2011[ 56 ]; Mostafalou et al, 2012[ 38 ]; Maqbool et al, 2016[ 30 ], 2017[ 31 ]; Pakravan et al, 2016[ 44 ]). Diazinon (O,O-diethyl O-[4-methyl-6-(propan-2-yl) pyrimidin-2-yl] phosphorothioate) (DZN) is an OP insecticide which is extensively used in agriculture and households (Pakzad et al, 2013[ 45 ]).…”
Section: Introductionmentioning
confidence: 99%